Split Cutter Method for Contact Stresses Research over Flank Surface of a Cutter; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Kozlov V. N. Victor Nikolayevich; Jia Yu Zhang; Jian Cui; Bogolyubova M. N. Mariya Nikitichna (2017, 2017)
Title screen